Market orientation of entrepreneurial university distance education and sustainable competitive advantage relationships: The mediating role of employee engagement - Paul Mensah Agyei; Chei Bukari; Nathaniel Amoah (Cogent Social Sciences)
To be competitive in the distance education service delivery market, the need for a strategic approach by managers of these institutions to manage the increased competition cannot be compromised. Despite the available past and current studies on market orientation, the impact of market orientation on firms in the context of distance education is yet to be explored. Additionally, given the COVID crisis, the increasing reliance on distance education has resulted in a dynamic and turbulent environment in which market orientation assumes even greater importance. This study seeks to examine the mediating role of employee engagement in the link between market orientation and sustainable competitive advantage. Using the multistage sampling technique, 375 respondents were selected, consisting of key management and staff of a certain university’s distance education programme. Analytically, partial least squares structural equation modelling (PLS-SEM) was used to address the various hypotheses of the study. Both customer and competitor orientations were found to have a significant positive effect on the university’s sustainable competitive advantage. The study’s outcomes will help shape policy and practise in distance education.